Sociological study of religiosity in post-atheist Kazakhstan - Zabirova, Aigul; Seitakhmetova, Natalya; Zhandossova, Sholpan; Nurov, Marhabbat (Frontiers in Sociology, 2025)
This paper explores a marked shift in the role and functions of religion in Kazakhstan, indicative of change in ideology and societal foundations. In explaining this shift, we highlight various elements that affect the religious landscape in Kazakhstan, with the most pronounced and recent trend being the Islamization of society. The subject of this study is the exploration a person's daily religious rituals, participation in religious activities, reading religious publications, and discussing religion with other people. Our analysis revealed that though many people identify themselves as religious, few participate in religious life daily. That is why we argue that Islam in Kazakhstan remains as a cultural and traditional value for many Muslims, rather than a vital component of their everyday life.